Extracellular matrix composition affects outgrowth of dendrites and dendritic spines on cortical neurons - Sharma, Archana; Hill, Katherine E.; Schwarzbauer, Jean E. (Frontiers in Cellular Neuroscience, 2023)
The composition of the extracellular matrix (ECM) in nervous tissue plays an important role in controlling neuronal outgrowth and synapse development. Changes in both protein and glycosaminoglycan components of the ECM occur with tissue injury and may affect neuron growth. To investigate neuron responses to alterations in fibronectin (FN), a major component of the wound ECM, we grew cortical neurons on cell-derived decellularized matrices composed of wild type FN (FN+/+) or of a mutant form of FN (FN∆/+) from which the III13 heparin-binding site had been deleted by CRISPR-Cas 9 gene editing. The most significant effect of the mutant FN was a reduction in dendrite outgrowth. Not only were dendrites shorter on mutant FN∆/+-collagen (COL) matrix than on wild type (FN+/+-COL) matrix, but the number of dendrites and dendritic spines per neuron and the spine densities were also dramatically reduced on FN∆/+-COL matrices. Mass spectrometry and immunostaining identified a reduction in tenascin-C (TN-C) levels in the mutant matrix. TN-C is an ECM protein that binds to the III13 site of FN and modulates cell-matrix interactions and has been linked to dendrite development. We propose that TN-C binding to FN in the wound matrix supports dendrite and spine development during repair of damaged neural tissue. Overall, these results show that changes in ECM composition can dramatically affect elaboration of neurites and support the idea that the ECM microenvironment controls neuron morphology and connectivity.